Real-World Implementation of Neurosurgical Enhanced Recovery After Surgery Protocol for Gliomas in Patients Undergoing Elective Craniotomy - Wang, Yuan; Xue, Ya-Fei; Zhao, Bin-Fang; Guo, Shao-Chun; Ji, Pei-Gang; Liu, Jing-Hui; Wang, Na; Chen, Fan; Zhai, Yu-Long; Wang, Yue; Xue, Yan-Rong; Gao, Guo-Dong; et al. (Frontiers in Oncology, 2022)
Objective: To design a multidisciplinary enhanced recovery after surgery (ERAS) protocol for glioma patients undergoing elective craniotomy and evaluate its clinical efficacy and safety after implementation in a tertiary neurosurgical center in China. Methods: ERAS protocol for glioma patients was developed and modified based on the best available evidence. Patients undergoing elective craniotomy for treatment of glioma between September 2019 to May 2021 were enrolled in a randomized clinical trial comparing a conventional neurosurgical perioperative care (control group) to an ERAS protocol (ERAS group). The primary outcome was postoperative hospital length of stay (LOS). Secondary outcomes were 30-day readmission rate, postoperative complications, duration of the drainage tube, time to first oral fluid intake, time to ambulation and functional recovery status. Results: A total of 151 patients were enrolled (ERAS group: n = 80; control group: n = 71). Compared with the control group, postoperative LOS was significantly shorter in the ERAS group (median: 5 days vs. 7 days, p<0.0001). No 30-day readmission or reoperation occurred in either group. The time of first oral intake, urinary catheter removal within 24 h and early ambulation on postoperative day (POD) 1 were earlier and shorter in the ERAS group compared with the control group (p<0.001). No statistical difference was observed between the two groups in terms of surgical- and nonsurgical-related complications. Functional recovery in terms of Karnofsky Performance Status (KPS) scores both at discharge and 30-day follow-up was similar in the two groups. Moreover, no significant difference was found between the two groups in the Hospital Anxiety and Depression Scale (HADS) scores. Conclusion: The implementation of the ERAS protocol for glioma patients offers significant benefits over conventional neurosurgical perioperative management, as it is associated with enhancing postoperative recovery, without additional perioperative complications and risks.